2020
DOI: 10.3390/app10041445
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Variation Effect of Aerodynamic Loads and Safety Analysis of Running Trains When Entering Tunnel Under Crosswind

Abstract: Sudden variation of aerodynamic loads is a potential source of safety accidents of high-speed trains (HSTs). As a follow-up investigation on the aerodynamic response of a HST that enters a tunnel under crosswind environment, this paper focuses on the transient response of a HST’s safety indices based on the train–track coupling interaction model. Firstly, a wind–train–track coupling dynamic model is proposed by introducing transient aerodynamic loads into the vehicle–track system. Secondly, the temporal evolut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Notably, due to the shielding effect of the tunnel walls, the crosswind's impact was limited to the exterior of the train, exerting a distinctive lateral force on this region [1]. Additionally, Yang et al studied the sudden variation effect of aerodynamic loads and safety analysis of running trains when entering tunnels under crosswind, focusing on the transient characteristics and main factors of aerodynamic loads [22]. Li et al confirmed through numerical simulation and field tests that the lateral vibration and aerodynamic drag of trains increased, and micro-pressure waves were produced at the tunnel exit when high-speed trains passed through tunnels [23].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, due to the shielding effect of the tunnel walls, the crosswind's impact was limited to the exterior of the train, exerting a distinctive lateral force on this region [1]. Additionally, Yang et al studied the sudden variation effect of aerodynamic loads and safety analysis of running trains when entering tunnels under crosswind, focusing on the transient characteristics and main factors of aerodynamic loads [22]. Li et al confirmed through numerical simulation and field tests that the lateral vibration and aerodynamic drag of trains increased, and micro-pressure waves were produced at the tunnel exit when high-speed trains passed through tunnels [23].…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of research works have been carried out on the HST crosswind safety assessment under different classical operation scenarios, such as tunnel, windbreak breach, bridge, embankment. 1,[3][4][5] It has been shown that the strong crosswind can cause train derailment and even overturning, which greatly threatens the safe operation of HSTs. In fact, the train overturning accidents owing to strong crosswind have been reported in many countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, each study focused on the single motion of the train, and the gas-solid-coupling motion of falling blocks under a train wind environment was overlooked. The driving safety under different natural environments [19][20][21] and infrastructure [22][23][24][25], as well as the safety of ancillary facilities in tunnels [26,27], under a train wind environment have been investigated in various works. However, the influence of spalling and falling blocks of high-speed-railway tunnel linings on driving safety has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%